2016
DOI: 10.1101/084897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal genomic surveillance ofPlasmodium falciparummalaria parasites reveals complex genomic architecture of emerging artemisinin resistance in western Thailand

Abstract: BackgroundArtemisinin-based combination therapies are the first line of treatment for Plasmodium falciparum infections worldwide, but artemisinin resistance (ART-R) has risen rapidly in in Southeast Asia over the last decade. Mutations in kelch13 have been associated with artemisinin (ART) resistance in this region.To explore the power of longitudinal genomic surveillance to detect signals in kelch13 and other loci that contribute to ART or partner drug resistance, we retrospectively sequenced the genomes of 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…We emphasize that this does not rule out involvement of other loci in other aspects of resistance such as fitness costs. A longitudinal genome sequencing study on a subset of the parasites examined here identified several regions of the genome that show rapid changes in SNP frequency, identifying several putative genome regions that may be selected by ART (Cerqueira et al 2015). Similarly, previous analyses have identified genome regions distant from kelch13 associated with ART-R (Cheeseman et al 2012; Miotto et al 2013; Takala-Harrison et al 2013; Cheeseman et al 2015; Miotto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize that this does not rule out involvement of other loci in other aspects of resistance such as fitness costs. A longitudinal genome sequencing study on a subset of the parasites examined here identified several regions of the genome that show rapid changes in SNP frequency, identifying several putative genome regions that may be selected by ART (Cerqueira et al 2015). Similarly, previous analyses have identified genome regions distant from kelch13 associated with ART-R (Cheeseman et al 2012; Miotto et al 2013; Takala-Harrison et al 2013; Cheeseman et al 2015; Miotto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lower levels of disease endemicity and acquired immunity in SEA strongly increase the likelihood that infected individuals will become symptomatic and thus will be treated with drugs. In Africa most infections are asymptomatic, hence the proportion of the parasite population exposed to ART selection is lower (Cerqueira et al, 2017, Nair et al, 2018.…”
Section: Detection Of Candidate Mutations In K13-propeller Domain Associated With Art Resistance In Huye Southern Rwanda In 2015mentioning
confidence: 99%
“…We emphasize that this does not rule out involvement of other loci in other aspects of resistance phenotype such as parasite fitness. A longitudinal genome sequencing study on a subset of the parasites examined in this paper identified several regions of the genome that show rapid changes in SNP frequency, identifying several other potential genome regions that may be selected by ART selection (42). Similarly, previous association analyses have identified other genome regions associated with ART-R other than the chr.…”
Section: Mutations Outside the Propeller Domain Are Associated With Smentioning
confidence: 63%